Analisis Pengaruh Variasi Material Elektroda Mesin EDM MP-50 Terhadap Kekasaran Permukaan Dan Ketirusan Lubang Pada Proses Pembuatan Dies Ring Baut - Riki Adi Haryanto; Ahmad Farid; Hadi Wibowo (Fakultas Teknik Universitas 17 Agustus 1945 Cirebon, 2019)
EDM machinery is currently growing, many small industries rely on EDM machines, especially in the design of molds and dies. The variation of electrodes on the EDM Singking machine greatly affects the results of roughness and taper in the process of making Dies, in order to produce a smooth product and the lowest taper value. The method used is an experiment using the MP-50 EDM machine by varying the electrode material of Copper, aluminum, and Carbon, the workpiece using ST 60 steel is sought for the results of the surface roughness and the smallest hole taper for the manufacture of ring bolt Dies. The results showed that the variation of electrode material (Copper, Aluminum, Carbon) greatly affects the surface roughness and hole taper in the EDM process. This is evidenced by the surface roughness values ​​of Copper=5.755µm, Aluminum=5.039µm, Carbon=8.218µm. The results of the hole taper test on Copper=0.667º, Aluminum=1.851º, Carbon=0.687º. Then from the results of the 3 electrodes, the smoothest level of surface roughness and the smallest hole taper will be determined to make ST60 steel bolt Diesring